Partial characterization of an extracellular lipase from Marinobacter sp through response surface methodology - Yadira, Fernández-Jerí, (2013)
In the last decade, has increased the demand for enzymes of microbial origin to diverse industrial processes. Therefore, the aim of these research was the partial biochemical characterization of an extracellular lipase of Marinobacter sp isolated from the Salinas de Pilluana (San Martin), using the response surface methodology. Were analyzed the effect of factors such as: pH (4,0 – 9,0), temperature (32,5 – 45,0 °C), time (0,0 – 40,0 min) and the concentrations of NaCl (0,0 – 10,0%) and CaCl2 (0,0 – 1,0%), on the specific activity through the Box-Behnken experimental statistical design employed in three levels. In addition, were determined the catalytic constants (Km and Vmax) and the thermal stability of the enzyme. The optimal reaction parameters to lipase from Marinobacter sp. were pH 7,0; 37 °C and 30 min, using as substrate p-nitrophenyl palmitate. The Vmax and Km of the lipase were 3,1900 U/mg and 0,2428 mM, respectively. The enzyme activity of lipase was stable up to 45 °C for 10 min.